2017
DOI: 10.1007/s00167-017-4505-y
|View full text |Cite
|
Sign up to set email alerts
|

High rate of recurrent patellar dislocation in skeletally immature patients: a long-term population-based study

Abstract: Retrospective case series, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
127
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(142 citation statements)
references
References 30 publications
9
127
1
5
Order By: Relevance
“…2,3 Studies have shown that lateral patellar instability patients are at risk of recurrence for up to 5 to 10 years, whereas most published studies perform 2 years' follow-up, which underestimates recurrence rates. 4 The MPFL site of injury appears multifocal, and thus, repair depends on accurate diagnosis of the location of injury. A magnetic resonance imaging study by Zhang et al 5 looked at the site of MPFL injury in pediatric patients and concluded that isolated femoral avulsion occurred in 32%, isolated patellar avulsion occurred in 39% and ligament stretch occurred in 4%; however, in 25%, there was more than 1 site of injury.…”
Section: See Related Article On Page 2909mentioning
confidence: 99%
“…2,3 Studies have shown that lateral patellar instability patients are at risk of recurrence for up to 5 to 10 years, whereas most published studies perform 2 years' follow-up, which underestimates recurrence rates. 4 The MPFL site of injury appears multifocal, and thus, repair depends on accurate diagnosis of the location of injury. A magnetic resonance imaging study by Zhang et al 5 looked at the site of MPFL injury in pediatric patients and concluded that isolated femoral avulsion occurred in 32%, isolated patellar avulsion occurred in 39% and ligament stretch occurred in 4%; however, in 25%, there was more than 1 site of injury.…”
Section: See Related Article On Page 2909mentioning
confidence: 99%
“…Patellar dislocation is a common disease among children and teenagers, and the incidence is over 30 per 100 000. Up to 71% of these patients may develop recurrent patellar instability, and 20% go on to suffer patellofemoral arthritis [6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Patella dislocation is a common disease among children and teenagers, and the incidence is over 30 per 100 000. Up to 71% of these patients may develop recurrent patella instability, and 20% go on to suffer patellofemoral arthritis [6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%